OPTIMIZATION OF HR POLICY FOR SUSTAINABLE SUCCESS IN BANKING SECTOR - Abdumo’minova Gavhar Erkinovna (Ecomind Press, 2025)
Banks operate in a dynamic and competitive environment, which requires strategic alignment of human resources policies. This ensures organizational efficiency, employee productivity and long-term sustainability. Effective management of HR policy is the fundamental foundation for the bank's success in changing market conditions, technological progress and regulatory requirements. In the banking system, human capital is considered as an important asset, therefore strategic management of HR policy is of particular importance.